Greek and Latin Expressions of Meaning : The Classical Origins of a Modern Metaphor - Andreas T. Zanker (C.H.Beck)
Verbs and nouns of meaning in ancient Greek and Latin are polysemous, just as in the case of the English verb (3z(Bto mean". Andreas T. Zanker considers how the ancient vocabulary could be used in different ways and investigates its development over time. In the first part of the book, Zanker argues for the role of metaphorical and metonymical transference in the creation of expressions of meaning; Greek and Roman authors used the same verbs to describe what inanimate things, including words and texts, meant/signified as they did of human beings in the act of meaning/signifying something. In the second part of the book, the author focuses on certain metaphorical extensions of this vocabulary and argues that they have implications for modern discussions of meaning, particularly in literary criticism.s
English
Keywords: linguistics; meaning; Latin; Greek